Suitability of Chicken EPGCS on Different Cryoprotective System - LI, B.C.; Chen, H.; Xiao, X.J.; Han, Wei; Xu, Qi; Xinsheng, Wu; Bao, Wenbin; Chen, G.H. (International Journal of Poultry Science, 2007)
The objective of this study was to evaluate the effect of three cryorotectants (at three concentration each) and two cryopreservation protocols on the preservation of chicken Primordial Germ Cells (PGCs) from gonads at stage 19 and stage 28. The PGCs were cryopreserved using Dimethylsulphoxide (DMSO; 10%, 20%, 30%), glycol (GLY; 10%, 20%, 30%), polyethylene glycol (PEG; 10%, 20%, 30%). In a first series of experiments, we compared viability after three cryorotectants based protocol I and found the viability of PGCs showed very significant percentage (86.53%) (p